A Community of Shared Future for Mankind—The Contemporary Development of the Social Foundations Theory of International Law*. (2nd January 2019) - Hui, Zhang
Abstract : In the traditional understanding, the social basis of the emergence and existence of international law can be summed up as an international society in which interstate conflict and cooperation and interests and contradictions coexist. In recent years, the term "international community" has been widely used in national practice and academic discourse. Many scholars believe that the development of interstate relations indicates that the international community is being transformed into a global international community. The concept of "a community of shared future for mankind" reflects China's new understanding of the social foundations of international law. It introduces Chinese traditional culture into global governance, develops Marxist theory on the community, is concerned both for mankind as a whole and for individuals, highlights the ultimate issues of the international community, and emphasizes the international community's union of diversity and interdependence. The idea of "a community of shared future for mankind" is of great significance for the theory and practice of international law; it reflects the emergence of methodological holism, the response of international law to the questioning of its legitimacy, and the trend toward hierarchical systematization in international law. The concept of "a community of shared future for mankind" is of great value to China's participation in the reform of the global governance system. It will help promote appreciation of the relations between China and the world, enhance China's international discourse power and discourse force, and promote the rule of law in international relations that China advocates.